Measuring Rates of Ubiquitin Chain Formation as a Functional Readout of Ligase Activity - Ronchi, Virginia P. (2012)
Specificity within the pathways of ubiquitin conjugation are defined by protein-binding affinities among the components. Enzyme kinetics provides a facile high-resolution experimental approach for quantitating such protein-binding affinities and yields additional mechanistic insights into the transition state of the enzyme-catalyzed reaction. Most ubiquitin ligases form free polyubiquitin chains at a slow rate in the absence of their cognate target protein as a normal step in their overall catalytic cycle. Rates of polyubiquitin chain formation can, therefore, be used as a reporter function kinetically to characterize binding interactions within the ligation pathway. We describe experimental approaches for: (1) precisely quantitating functional E1 and E2 concentrations by their stoichiometric formation of (125)I-ubiquitin thiolester; (2) semiquantitative screens to define the cognate E2(s) for ubiquitin ligases based on their ability to support polyubiquitin chain formation; (3) initial rate studies to quantify K(m) and k(cat) as a measure of the ability of specific E2-ubiquitin thiolester substrates to support ligase-catalyzed polyubiquitin chain formation; and (4) an isopeptidase T-based technique for distinguishing between free and conjugated polyubiquitin chains formed in the functional assays. These kinetic methods provide mechanistic insights that are otherwise inaccessible by other experimental approaches and yield a precision in characterizing protein interactions that exceeds that of other techniques.